Gender in Japanese Popular Culture Rethinking Masculinities and Femininities - Salenius, Sirpa (Springer Nature, 2023)
This open-access essay collection brings together a range of viewpoints on gender from a diverse group of international scholars based in Finland, Belgium, Japan, Singapore, and Australia. The focus is, in particular, on gender performativity and non-binary or non-normative gender. The essays examine the ways in which gender can be depicted, perceived, and understood in Japanese popular culture. The work will be of interest to scholars working in gender studies, Asian studies, and popular culture. It will also act as a source text for higher education courses in Asia, Europe, and the United States.